ANALISIS KINERJA PENGELOLA PELABUHAN PERIKANAN NUSANTARA PEKALONGAN, JAWA TENGAH - Nasir, Hamdan; Rosyid, Abdul; Wijayanto, Dian (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Performance is basically the result obtained by a person or agency in performing a particular job. The purpose of this research were identified the performance management, evaluated the performance, and analyzed the performance level Pekalongan Fishing Port. Descriptive method was used in this study. Purposive sampling was used for sampling method. Object of this research was management of Pekalongan Fishing Port and customers satisfaction. Data analysis methods used were test validity, test reliability, Customer Satisfaction Index, Importance and Performance Analysis and gap analysis. The test results show the validity declared invalid, because r value bigger than r table is 0.444 for 20 employees. While the customer is 0.229 for 74 customers. Attributes of reliability test results for 0.632 and 0.832 employees, while the attributes of reliability test of 0.413 and 0.492 customers. From the research results of the identification of performance management are implementation of fishing harbors operational service of fisheries, fish resources management activities, implementation of the system of quality assurance and safety of fishery products. The results of performance evaluation in 2011 classified optimal, because get 74 of the results optimum conditions, 100. While the results for employee satisfaction index was 77 % and 80.4 % for customers.